2014
DOI: 10.1186/1471-2458-14-1230
|View full text |Cite
|
Sign up to set email alerts
|

The accessibility and acceptability of self-management support interventions for men with long term conditions: a systematic review and meta-synthesis of qualitative studies

Abstract: BackgroundSelf-management support interventions can improve health outcomes, but their impact is limited by the numbers of people able or willing to access them. Men’s attendance at existing self-management support services appears suboptimal despite their increased risk of developing many of the most serious long term conditions. The aim of this review was to determine whether current self-management support interventions are acceptable and accessible to men with long term conditions, and explore what may act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 87 publications
(271 reference statements)
16
80
0
Order By: Relevance
“…This reflects the current provision of care, but men were also interested in a question‐and‐answer session with their rheumatologist or specialist nurse, opportunities to hear about current research, and education sessions for symptom management. This is similar to evidence from studies of other long‐term conditions suggesting that support services for men should have a practical focus 16 and provide opportunities to gather new information 22, 23 and that men use information exchange as a form of emotional support 24. Despite this finding, men are underrepresented in trials focusing on symptom management in RA (e.g., in a fatigue management program, 85.4% of the participants were female) 25.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This reflects the current provision of care, but men were also interested in a question‐and‐answer session with their rheumatologist or specialist nurse, opportunities to hear about current research, and education sessions for symptom management. This is similar to evidence from studies of other long‐term conditions suggesting that support services for men should have a practical focus 16 and provide opportunities to gather new information 22, 23 and that men use information exchange as a form of emotional support 24. Despite this finding, men are underrepresented in trials focusing on symptom management in RA (e.g., in a fatigue management program, 85.4% of the participants were female) 25.…”
Section: Discussionsupporting
confidence: 69%
“…Male participants were less interested than women in hearing from other RA patients, which may reflect men's preferences for seeking out information rather than experiences 16. Although this may call into question the appropriateness of providing interventions involving co‐delivery with patients for men, previous qualitative work found that co‐facilitation by a patient research partner in focus groups was helpful for engaging men in discussion 8.…”
Section: Discussionmentioning
confidence: 96%
“…Self-management interventions focus on enhancing patients' ability and 5 confidence to manage their condition effectively by providing education, training and support to develop their 6 knowledge, skills and both internal and external resources [3]. They have been developed for a range of different 7 long-term conditions and can take a variety of forms (e.g., lay or professionally led, generic or disease-specific,…”
mentioning
confidence: 99%
“…Despite these potential benefits, significant gaps remain in understanding which aspects 15 of self-management interventions work best, in what circumstances, and for whom [3,10]. A substantial…”
mentioning
confidence: 99%
See 1 more Smart Citation